Effect of bio-enhancers and bio-fertilizers on physiological losses in weight, spoilage and shelf-life of Mango (Mangifera indica) cv. Amrapali - BHADAURIA, ANKIT SINGH; TRIPATHI, VIVEK KUMAR (The Indian Journal of Agricultural Sciences, 2025)
The present experiment was conducted during 2020–21 and 2021–22 at Chandra Shekhar Azad University of Agriculture and Technology, Kanpur, Uttar Pradesh to determine the effect of bio-enhancers and bio-fertilizers on physiological losses in weight, spoilage and shelf-life of Mango (Mangifera indica L.) cv. Amrapali during storage (25°C±1; 60–65% RH) for 3, 5, 7, 9, 11, 13, and 15 days. The experiment was laid out in randomized block design (RBD) having seven treatments [T1, FYM (25 kg/tree/year) + Organic mulch (Paddy straw); T2, FYM (25 kg/tree/ year) + Organic mulch + Amritpani (20%) + Azotobacter (100 g/tree); T3, FYM (25 kg/tree/year) + Organic mulch + Panchagavya (3%) + Azotobacter (100 g/tree); T4, FYM (25 kg/tree/year) + Organic mulch + Jivamrit (20%) + Azotobacter (100 g/tree); T5, FYM (25 kg/tree/year) + Organic mulch + Amritpani (20%) + PSB culture (100 g/ tree); T6, FYM (25 kg/tree/year) + Organic mulch + Panchagavya (3%) + PSB culture (100 g/tree); T7, FYM (25 kg/tree/year) + Organic mulch + Jivamrit (20%) + PSB culture (100 g/tree), respectively] in three replications. The experimental results revealed that T3 group was recorded significantly higher in TSS (°Brix) and total sugar content (%) followed by T6 and T4 groups. Meanwhile, PLW (%), titratable acidity content (%) and spoilage (%) were found minimum in T3 group followed by T6 and T4 groups. Thus, on the basis of the above results, it may be suggested that bio-enhancers and bio-fertilizers could be applied in mango cultivation under the sub-tropical plains of Central Uttar Pradesh, India.